Holitouch: Conveying Holistic Touch Illusions by Combining Pseudo-Haptics With Tactile and Proprioceptive Feedback During Virtual Interaction With 3DUIs - Ariza Nunez, Oscar Javier; Zenner, André; Steinicke, Frank; Daiber, Florian; Krüger, Antonio (Frontiers in Virtual Reality, 2022)
Virtual reality technology and immersive virtual environments often support realistic hand representations via hand-posture-sensing controllers or hand tracking for natural hand-based interaction. However, one limiting factor remains as the lack of realistic haptic feedback including tactile and proprioceptive cues; even for simple haptic interactions like touching a virtual object. This paper introduces the Holitouch technique to improve the haptic realism of essential 3D user interface elements such as buttons. Holitouch is a feedback technique based on a wearable device that combines different types of haptic feedback (i.e., (i) pseudo-haptic, (ii) tactile, and (iii) proprioceptive) to convey the holistic sensation of stiffness, contact, and activation while interacting with 3D buttons. Our approach provides these sensations by utilizing redundant multisensory cues, i.e., congruent feedback, to create plausible illusions of touch. The results of two experiments show that the proposed feedback combination contributes to delivering a holistic sensation when interacting with buttons in VR while having high user acceptance.